PERFORMANCE ANALYSIS OF TEACHER DEVELOPMENT BUDGET EFFICIENCY BASED ON DATA ENVELOPMENT ANALYSIS (DEA): A CASE STUDY AT SDN TELUKJAMBE TIMUR FOR THE 2023-2024 FISCAL YEAR - Acih Trisnawati; Maman Suryaman; Slamet Sholeh (RADJA PUBLIKA, 2026)
This study aims to analyze the efficiency level of teacher development budget management in six public elementary schools in Telukjambe Timur District for the 2023–2024 fiscal year using the Data Envelopment Analysis (DEA) approach with a CCR model with an input orientation. Input variables consist of the teacher development budget and the number of teachers, while output variables include the number of development activities and the Teacher Performance Assessment (PKG) score. The quantitative approach is supported by qualitative data through interviews to enrich the interpretation of the results. DEA findings indicate that the efficiency level between schools is unstable and tends to decline. In 2023, there were two efficient schools, while in 2024, no schools reached the efficiency frontier. Inefficiency mainly stems from budget overruns and a lack of development activities that are far below the DEA projection, even though the PKG score in 2024 is in optimal condition. Qualitative results show that budget planning is not fully needs-based, activity implementation is hampered by delays in BOS disbursement, and monitoring and evaluation do not utilize data optimally. This study recommends strategic improvements through strengthening data-driven planning, optimizing teacher development activities, improving documentation, and implementing continuous monitoring and evaluation. Overall, the research confirms that budget efficiency is not only determined by the size of input, but also by the quality of governance of teacher development programs.